Empirical verification of a measurement related to the excessive alcohol consumption in brazilians - Formiga, Nilto S. (2015)
The consumption of alcohol in college students has been a crucial problem for interpersonal relationships and academic development; but it is also a problem that means a social, economic and health damage. It has been emerged and suggested measures to be ratified to identify the phenomenon of alcohol consumption. However, the Alcohol Use Disorders Identification Test (AUDIT) is still the most used instrument in world studies, the same one that has remained constant. The present research aims to assess the internal and factorial consistency of the AUDIT in college students from different Brazilian States. A total of 639 college students of both sexes over 18 years old, distributed in different advanced courses of public and private institutions in four Brazilian States, responded the AUDIT and socio-demographic data. Performing different statistical calculations, psychometric indicators were observed which gave confidence to the AUDIT measurement in the investigated sample. This procedure guaranteed the measure regarding the identification of the alcohol consumption problem, as it also observed that independent of the educational context of college students in the concerned Brazilian States, all respondents revealed problems with alcohol consumption.